2003
DOI: 10.1146/annurev.immunol.21.120601.140946
|View full text |Cite
|
Sign up to set email alerts
|

CD45: A Critical Regulator of Signaling Thresholds in Immune Cells

Abstract: Regulation of tyrosine phosphorylation is a critical control point for integration of environmental signals into cellular responses. This regulation is mediated by the reciprocal actions of protein tyrosine kinases and phosphatases. CD45, the first and prototypic receptor-like protein tyrosine phosphatase, is expressed on all nucleated hematopoietic cells and plays a central role in this process. Studies of CD45 mutant cell lines, CD45-deficient mice, and CD45-deficient humans initially demonstrated the essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
773
3
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 778 publications
(814 citation statements)
references
References 184 publications
16
773
3
9
Order By: Relevance
“…S1). Panleukocyte anti-CD45 antibodies were coupled to APC-tandem dyes labeled lymphocytes, monocytes, and polymorphonuclear leukocytes (19) (Figs. 1A and 1B, left panels).…”
Section: Resultsmentioning
confidence: 99%
“…S1). Panleukocyte anti-CD45 antibodies were coupled to APC-tandem dyes labeled lymphocytes, monocytes, and polymorphonuclear leukocytes (19) (Figs. 1A and 1B, left panels).…”
Section: Resultsmentioning
confidence: 99%
“…Cross-linking CD45 may favor dimerization and thus reduces PTPase activity predominantly in CD45R0 + T cells [29,42], possibly due to the fact that CD45R0 molecules undergo the least extracellular sialylation and O-glycosylation. In fact, PTPase activity of CD45R0 + T cells was reduced to levels almost comparable to CD45RA + T cells following CD45 cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a membrane protein tyrosine phosphatase, CD45, positively regulates Lyn by dephosphorylating Y-507, which causes a conformational change that reveals the catalytic domain of Lyn and promotes autophosphorylation of the positive regulatory tyrosine at position 396 (Y-396) (20,21). This model is supported by studies of CD45 Ϫ/Ϫ B lymphocytes, in which it has been shown that Y-507 in Lyn is hyperphosphorylated and that BCR-mediated signaling is attenuated (22).…”
mentioning
confidence: 98%